Upaya Peningkatan Kualitas Pendidikan Agama di Perguruan Tinggi Umum - Kasuwi Kasuwi (Universitas Negeri Malang, 2016)
Corruption is often viewed as a social disease representing an endemic problem. The corruption in Indonesia is seriously increasing due to the slow law process of corruption, the non-discouraging effect of the corruption punishment, the easily-spread corruption behaviour, the corruption rooted from traditional values, and the non-transparent governance. Preventive and corrective actions should be taken to deal with corruption, one of which is through public learning.